CHISEL PLOW TOOLS CONSUMING BY THE SOIL ABRASION - BOLZANI, ATÍLIO; BEJARANO, JOSÉ MIGUEL ZELAYA; COLET, MARCELO JOSÉ; SVERZUT, CLÁUDIO BIANOR (Revista Brasileira de Engenharia de Biossistemas, 2007)
In conventional management of the soil, the quality of the agricultural tillage operations affects thecrop yield. In the chisel plowing, some factors influence the results, as like the form and size of theused tool. The objective of this work was to evaluate the consuming occurred in a set of toolsduring the agriculture operation of soil chisel plowing. Two agricultural fields, one with 14 andanother one with 11,5 hectares had been chisel plowed. The soil of second field was of texturecoarser than of the first one. The consuming was evaluated by the determination of the mass ofthe set of five tips of the chisel plow, before and after the work. The loss of mass was of 188,3 g inthe first field and of 225,5 g in second, the equivalent 7,4 and 9,5 % of the mass of a new tip,respectively. Although to be a smaller field, the highest loss of mass occurred in the area with thehighest sand contend.